KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP - Gita; Yunus; Haerun Ana (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2024)
This study aims to describe the ability to write explanatory texts among eighth-grade students at SMP Negeri 1 Kabawo. The research method used is quantitative descriptive with field research. A sample of 105 students was selected using proportionate stratified random sampling from six classes. Data on the ability to write explanatory texts were obtained through written tests and interviews with teachers and students. The results show that out of 105 sampled students, 81 students (77%) are considered proficient and 24 students (23%) are considered not yet proficient in writing explanatory texts. Classically, the ability to write explanatory texts among eighth-grade students at SMP Negeri 1 Kabawo is considered inadequate. The percentage of students who achieve the minimum proficiency level (77%) is still below the classical mastery criteria (85%). Evaluation of assessment aspects indicates that most students have not yet reached the expected level in several aspects such as the suitability of topics with content, language rules, and accuracy in spelling and punctuation.